JAK1/2 Inhibitor Baricitinib Improves Skin Fibrosis and Digital Ulcers in Systemic Sclerosis - Hou, Zhanying; Su, Xuehan; Han, Guangming; Xue, Ruzeng; Chen, Yangxia; Chen, Ye; Wang, Huan; Yang, Bin; Liang, Yunsheng; Ji, Suyun (Frontiers in Medicine, 2022)
Background Systemic sclerosis (SSc) is a rare disabling connective tissue disease with few available treatment options. Diffuse cutaneous systemic sclerosis (dcSSc) is associated with high mortality. A previous experiment has shown that JAK2 inhibitor can significantly improve skin fibrosis in bleomycin (BLM)-induced murine model, including reducing dermal thickening and collagen accumulation. We aimed to describe the efficacy of oral JAK1/2 inhibitor baricitinib in SSc patients, especially focusing on skin fibrosis and microvascular manifestations. Methods We described the different effects of oral selective JAK1, JAK2, or JAK3 inhibitor treatment in a BLM-induced skin fibrosis mouse model. Furthermore, 10 adult patients with dcSSc were treated with baricitinib. We assessed the changes in modified rodman skin score (mRSS) and digital ulcer net burden at week 12 and 24 from baseline. We also compared the absolute changes in scores on the Scleroderma Health Assessment Questionnaire (SHAQ) and a total score on the St. George's Respiratory Questionnaire (SGRQ) over a 24-week period. Results In the experimental mouse model of skin fibrosis, a JAK1 and JAK2 inhibitor ameliorated skin fibrosis, and a JAK2 inhibitor had the most obvious effect. Treatment with the JAK2 inhibitor also blunted the capillary rarefaction. We demonstrated that skin fibrosis and digital ulcers were significantly relieved in 10 SSc patients treated with baricitinib. The mRSS significantly improved at week 12 from baseline, with a mean change in mRSS of −8.3 [95% confidence interval (CI), −12.03 to −4.574; p = 0.0007] and improved greater at week 24 to −11.67 (95% CI, −16.84 to −6.496; p = 0.0008). Among the four patients with digital ulcers (DU), three were completely healed at week 24, the number of ulcers in another patient was significantly reduced, and there was no patient with new ulcers. Only one adverse event (AE) of herpes zoster was observed. Conclusions Our results indicate that selective JAK1 and JAK2 inhibitor alleviates skin fibrosis, and oral JAK1/2 inhibitor baricitinib is a potentially effective treatment for dcSSc patients with skin fibrosis and DU. Baricitinib was well-tolerated by most patients in this study. Additional large clinical trials are needed to confirm our pilot findings. Chinese Clinical Trial Registry Number ChiCTR2000030995.